2022
DOI: 10.1186/s12884-022-04938-y
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of non-invasive methods for assessing the progress of labor in the first stage: a systematic review and meta-analysis

Abstract: Background The World Health Organization in recent years has emphasized reducing the possibility of unnecessary interventions in natural childbirth, but little is known about the accuracy of non-invasive methods when assessing the progress of labor. This paper presents a literature review to assess strategies that support non-invasive methods for labor during the first stage. It evaluates the available evidence to provide the most suitable assessments and predictions that objectively identify t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…30 A systematic review conducted by Pan et al showed that an OSA > 100 to 126 can predict normal vaginal delivery, but <126 has significantly longer first and second stages of labor and a higher rate of requiring cesarean section. 46 HPD data can be used to predict the engaged fetal head, assess labor progress, and predict the mode of delivery. The AOP data can be used to evaluate labor progress and predict the mode of delivery, with an AOP of 93-120 indicating a high likelihood of normal labor progression with a sensitivity of 52%-92%.…”
Section: Evaluation Items To Accurately Assess Progressmentioning
confidence: 99%
“…30 A systematic review conducted by Pan et al showed that an OSA > 100 to 126 can predict normal vaginal delivery, but <126 has significantly longer first and second stages of labor and a higher rate of requiring cesarean section. 46 HPD data can be used to predict the engaged fetal head, assess labor progress, and predict the mode of delivery. The AOP data can be used to evaluate labor progress and predict the mode of delivery, with an AOP of 93-120 indicating a high likelihood of normal labor progression with a sensitivity of 52%-92%.…”
Section: Evaluation Items To Accurately Assess Progressmentioning
confidence: 99%
“…Over the years, it has become a matter of debate whether a vaginal examination is the most appropriate method to evaluate labour progression, since it is an invasive procedure associated with pain, embarrassment, potential infection, and possible chorioamnionitis [ 7 ]. Moreover, there is inconsistency in examinations with a report that two different clinicians differed in cervical dilatation measurements by 2 cm or more in 11% of occasions [ 1 ].…”
mentioning
confidence: 99%
“…Another study showed that the mean number of vaginal examinations was three when the average labour duration was 8 h, but most importantly, the maximum number of examinations was 11 in some cases [ 9 ]. For these reasons and in conjunction with the current interest worldwide to support normality at childbirth, there is an attempt in the literature to identify and re-introduce in clinical practice alternative and less intrusive means of labour progress assessment [ 6 , 7 ].…”
mentioning
confidence: 99%
See 2 more Smart Citations